Understanding adolescent behavior and victimization of special populations through Bronfenbrenner’s bioecological theory - Williams, York (Victimology, 2022)
Bronfenbrenner suggests that we can understand the developmental milieus of children through the lens of their micro-, macro-, and meso-systems of supports. This framework becomes critical when we consider the trauma histories that may result from such exposure to adverse or tragic events that may also procure crisis responses from schools, communities, and organizations. Since adolescents are a high-risk student population, it is important to support tiered preventions as well as interventions at various social cultural levels with interagency linkages between home, school, and community. This chapter provides a conceptual lens around adolescent behavior with an understanding of victimization of youth through Bronfenbrenner’s framework. Recommendations are offered on how best to support this growing population with an understanding of trauma informed instruction and supports offered in settings from school, community, agency, and religious institutions.